Temperature Diagrams of Eutectoid Steel Heating - A. P. Nesenchuk; S. S. Kovalev; T. V. Ryzhova; A. V. Matusevich; V. V. Begliak (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Problems pertaining to power- and resource-saving while heating eutectoid steel in furnaces of mechanical engineering, automotive and tractor plants (blanking and mechanical assembly production) are considered in the paper. The paper shows that a heating device according to its heating technical parameters must be developed with due account of a temperature diagram having properties which are peculiar to the heated charge.